Skeletal muscle growth dynamics and the influence of first-feeding diet in Atlantic cod larvae (Gadus morhua L.) - Vo, Tu Ahn; Galloway, Trina Falck; Bardal, Tora; Halseth, Christine K.; Øie, Gunvor; Kjørsvik, Elin (Biology Open, 2016)
Dynamics between hypertrophy (increase in cell size) and hyperplasia (increase in cell numbers) of white and red muscle in relation to body size [standard length (SL)], and the influence of the first-feeding diets on muscle growth were investigated in Atlantic cod larvae (Gadus morhua). Cod larvae were fed copepod nauplii or rotifers of different nutritional qualities from 4 to 29 days post hatching (dph), Artemia nauplii from 20 to 40 dph and a formulated diet from 6 to 60 dph. The short period of feeding with cultivated copepod nauplii had a positive effect on both muscle hyperplasia and hypertrophy after the copepod/rotifer phase (19 dph), and a positive long term effect on muscle hypertrophy (60 dph). The different nutritional qualities of rotifers did not significantly affect muscle growth. We suggest here a model of the dynamics between hyperplasia and hypertrophy of red and white muscle fibre cells in relation to cod SL (4 to 30 mm), where the different red and white muscle growth phases clearly coincided with different metamorphosis stages in cod larvae. These shifts could be included as biomarkers for the different stages of development during metamorphosis. The main dietary muscle effect was that hypertrophic growth of red muscle fibres was stronger in cod larvae that were fed copepods than in larvae that were fed rotifers, both in relation to larval age and size. Red muscle fibres are directly involved in larval locomotory performance, but may also play an important role in the larval myogenesis. This can have a long term effect on growth potential and fish performance. © 2016. Published by The Company of Biologists Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution and reproduction in any medium provided that the original work is properly attributed.